The floods in north India in 1988- Forecasting aspects - SINGH, RANJIT (MAUSAM, 1992)
Severe floods/flash floods ravaged the States of Jammu& Kashmir, Haryana, Himachal Pradesh and Punjab during, (i) 2nd half of July and last half of August 1988. and (ii) 4th week of September 1988. They took place when heavy rains occurred in these States due to the interaction of mid-latitude westerly troughs with the monsoon pulses In the form of equatorial zones of maximum cloudiness (EZMC), located south of 20 N. Satellite pictures and synoptic charts suggest that: (a) The systems which formed in July-August 1988 were fed by moisture mainly from the Arabian Sea and had tropical characteristic, and (b) The systems which formed in SejJtember.198.8 had their moisture supply both from the Arabian Sea and the Bay of Bengal and were extra-tropical in character.. The paper describes two of these events in detail. The satellite picture3 show cloud formation resulting in heavy rains.